Determination of Deformations as a Result of Seismic Loadings on Two‐Dimensional Reinforced Concrete Frame via Terrestrial Laser Scanners. Issue 2 (18th October 2011) - Ceylan, A.; Gümüş, M.
<x xml:space="preserve">Abstract</x> Parallel to the technological developments, methods of defining locational data are changing. Laser scanners bring new advantages to engineering measurements and geodesy. Terrestrial laser scanners, which have previously been used in map engineering, have become an alternative method of measurement, especially for terrestrial applications. A common characteristic of deformation measurements is the requirement to measure the location of sufficient reference and object points established on the monitored structure. The number of reference and object points is limited when using classical methods, but not when using a laser scanner. Due to the limitations of classical geodetic survey methods, such as difficulty of application, high costs and low production speed, the present study applied ground laser scanners to deformation monitoring. A two‐dimensional (2D) deformation survey was made of a concrete frame placed on a loading wall. Cartesian coordinates, derived from survey and evaluations, were converted into a standard coordinate system using the Molodensky–Badekas 3D similarity transformation. Student's t test has been used to determine whether it was significant with the difference of coordinates or not. The deformation amounts and directions obtained from the electronic tachymeter and ground laser scanners were found to be very similar.